Diseño y construcción de un sistema informático de cálculo y gestión para el tratamiento de prendas de vestir "MADELEN" en la fábrica lavamodas JEAN'S en la ciudad de Ambato. - Mendoza Cabrera, José Luis (2010)
The exposed project of Thesis consists on the Design and construction of a computer system of calculation and administration for the treatment of garments of dressing "Madelen" in the factory LAVAMODAS JEAN'S in the city of Ambato. This work seeks to show the utility of having a system of industrial administration in the region center of the country, based on the application of technologies of information to adapt the software to the necessities of each process that it includes the treatment of garments. Based on the requirements that this software type uses he is carried out the design from the application to measure "MADELEN" whose main characteristic is the use of you formulate for each type of treatments that they are included in an offer program on the part of it Manufactures it and the handling of each one of the elements included in the process. It consists of four main modules with different functionality but in common union to take the productive cycle of factory at an excellence level. The control of revenues of garments is the first part or the beginning of the process, through the first I modulate it is controlled and it registers the entrance of garments that each one of the clients takes to it manufactures it for its respective treatment, making consist the detail of garments and value to get paid in a receipt as justification. The process cycle continues with the creation of an modulate that it negotiates and it calculates through you formulate the entered data, giving as a result final a report with percentages and names of each one of the chemists that they will be used in the treatment of each one of the garments. In this same event he unites another factor that controls the quantity of each one of the existent chemists in stock, upgrading the data in real time to the moment to carry out the calculations. After having carried out each calculate and position in march the labor side of the factory, like final part of the process is carried out the delivery of the garments with the help of the information that is granted through the receipt in a beginning, this last step it analyzes the I number of entered garments and given validating its correct delivery in number and service. Outside of the productive process, it includes a range you reports characteristic of the necessities that it manufactures it in if it possesses, information that is granted in real time and with exact data according to the taken production. With the purpose of giving learning easiness in the handling of the software is elaborated in user's manual in which is detailed from way didactic step to step the use of the software whose copy rests in the present thesis.